Effects of different agricultural wastes on the dissipation of PAHs and the PAH-degrading genes in a PAH-contaminated soil. (April 2017) - Han, Xuemei; Hu, Hangwei; Shi, Xiuzhen; Zhang, Limei; He, Jizheng
Abstract: Land application of agricultural wastes is considered as a promising bioremediation approach for cleaning up soils contaminated by aged polycyclic aromatic hydrocarbons (PAHs). However, it remains largely unknown about how microbial PAH-degraders, which play a key role in the biodegradation of soil PAHs, respond to the amendments of agricultural wastes. Here, a 90-day soil microcosm study was conducted to compare the effects of three agricultural wastes (i.e. WS, wheat stalk; MCSW, mushroom cultivation substrate waste; and CM, cow manure) on the dissipation of aged PAHs and the abundance and community structure of PAH-degrading microorganisms. The results showed that all the three agricultural wastes accelerated the dissipation of aged PAHs and significantly increased abundances of the bacterial 16S rRNA and PAH-degrading genes (i.e. pdo1 and nah ). CM and MCSW with lower ratios of C:N eliminated soil PAHs more efficiently than WS with a high ratio of C:N. Low molecular weight PAHs were dissipated more quickly than those with high molecular weight. Phylogenetic analysis revealed that all of the nah and C12O clones were affiliated within Betaproteobacteria and Gammaproteobacteria, and application of agricultural wastes significantly changed the community structure of the microorganisms harboring nah and C12O genes, particularly in the CM treatment. Taken together, our findings suggest that the three tested agricultural wastes could accelerate the degradation of aged PAHs most likely through changing the abundances and community structure of microbial PAH degraders. Highlights: Three agricultural wastes were used to a 90-day soil microcosm study. Agricultural wastes accelerated dissipation of the aged PAHs in soil microcosms. Agricultural wastes with lower C:N ratios eliminated the aged PAHs more quickly. Agricultural wastes significantly increased abundances of the PAH-degrading genes. Agricultural wastes obviously changed the community structure of PAH-degraders.